Stages of Teaching a Foreign Language - Ergashovna, Kultayeva Feruza (European Journal of Life Safety and Stability (2660-9630), 2022)
The method of teaching foreign languages is not limited to the connection with the specified basic sciences, but uses the knowledge and methods of other, so-called related sciences. So, the general outlines of the learning process can be represented in terms of cybernetics - a science, the subject of which is the control processes occurring in complex dynamic systems. Cybernetic analysis of pedagogical phenomena contributes to a clearer isolation of the interrelated links and conditions of the pedagogical process, allows you to introduce elements of programmed teaching into teaching foreign languages. The programmed methods solve the problem of optimizing the management of the educational process.